Concordance of regional hypoperfusion by pCASL MRI and 15O-water PET in frontotemporal dementia: Is pCASL an efficacious alternative? - Ssali, Tracy; Narciso, Lucas; Hicks, Justin; Liu, Linshan; Jesso, Sarah; Richardson, Lauryn; Günther, Matthias; Konstandin, Simon; Eickel, Klaus; Prato, Frank; Anazodo, Udunna C.; Finger, Elizabeth; et al. (NeuroImage clinical, 2022)
•ASL is an alternative to 15O-water for identifying hypoperfusion in FTD patients.•ROI-based perfusion by ASL and 15O-water were strongly correlated (R > 0.75).•Hypoperfusion patterns identified by 15O-water and ASL were in good agreement.•Careful selection of the reference region is required to avoid erroneous results. Clinical diagnosis of frontotemporal dementia (FTD) remains a challenge due to the overlap of symptoms among FTD subtypes and with other psychiatric disorders. Perfusion imaging by arterial spin labeling (ASL) is a promising non-invasive alternative to established PET techniques; however, its sensitivity to imaging parameters can hinder its ability to detect perfusion abnormalities. This study evaluated the similarity of regional hypoperfusion patterns detected by ASL relative to the gold standard for imaging perfusion, PET with radiolabeled water (15O-water). Perfusion by single-delay pseudo continuous ASL (SD-pCASL), free-lunch Hadamard encoded pCASL (FL_TE-pCASL), and 15O-water data were acquired on a hybrid PET/MR scanner in 13 controls and 9 FTD patients. Cerebral blood flow (CBF) by 15O-water was quantified by a non-invasive approach (PMRFlow). Regional hypoperfusion was determined by comparing individual patients to the control group. This was performed using absolute (aCBF) and CBF normalized to whole-brain perfusion (rCBF). Agreement was assessed based on the fraction of overlapping voxels. Sensitivity and specificity of pCASL was estimated using hypoperfused regions of interest identified by 15O-water. Region of interest (ROI) based perfusion measured by 15O-water strongly correlated with SD-pCASL (R = 0.85 ± 0.1) and FL_TE-pCASL (R = 0.81 ± 0.14). Good agreement in terms of regional hypoperfusion patterns was found between 15O-water and SD-pCASL (sensitivity = 70%, specificity = 78%) and between 15O-water and FL_TE-pCASL (sensitivity = 71%, specificity = 73%). However, SD-pCASL showed greater overlap (43.4 ± 21.3%) with 15O-water than FL_TE-pCASL (29.9 ± 21.3%). Although aCBF and rCBF showed no significant differences regarding spatial overlap and metrics of agreement with 15O-water, rCBF showed considerable variability across subtypes, indicating that care must be taken when selecting a reference region. This study demonstrates the potential of pCASL for assessing regional hypoperfusion related to FTD and supports its use as a cost-effective alternative to PET.